The Development of Translation Capability for the Holy Quran of Student of Teacher Candidate for Islamic Religious Education: A Tamyiz Learning and Teaching Strategy - Aam Abdussalam; Saepul Anwar; Anwar Taufik Rahmat (Universitas Negeri Jakarta, 2019)
It has become a Global Issue that the quality of education will never exceed the quality of teachers. Therefore, improving the quality of teachers should be the main priority of every party concerned about the quality of education, including religious education in schools. Therefore, improving the quality of Islamic Religious Education (IRE) teachers needs to be a priority for every educational institution that prints candidates for religious teachers, one of which is the study program of Islamic Education Science (IPAI) at Universitas Pendidikan Indonesia (UPI) as part of efforts to improve religious education in schools. One of the competencies that IRE teachers need to have is the ability to translate the Quran. Related to this matter, this paper specifically describes how the implementation of tamyÃ®z method to improve the ability of the student to translate the Quran as prospective teachers of IRE at Schools. The tamyÃ®z method is an innovative method of learning Arabic developed by Abaza, M.M. This paper used qualitative research with descriptive method